Comparative Study on Biological Activities and Chemical Profiling of Mushroom (Pleurotus pulmonarius (Fr.) Quel.) Cultured on Lignocellulosic Agro Wastes - Nor Hisam, Zamakshshari; Idris Adewale, Ahmed; Muhammad Nazil Afiq, Nasharuddin; Nurul Syahira, Zaharudin; Najihah, Mohd Hashim; Rozana, Othman (John Wiley & Sons, Inc, 2023)
The relevance of the lignocellulosic substrate in the cultivation of mushrooms has lent support to the exploration of several lignocellulosic agro wastes. This study was, thus, aimed at the evaluation of durian peel as an alternative substrate for more sustainable mushroom cultivation and climate change mitigation. The secondary metabolites and biological activities of both aqueous and organic mushroom (Pleurotus pulmonarius (Fr.) Quel.) extract cultured on durian peel and rubberwood sawdust substrate were compared using GCMS, LCMS as well as various biological assays (cytotoxicity, antimicrobial and antioxidant activities). Mushroom extracts from durian peel substrates possess remarkable biological activities. The results showed that the aqueous extracts had poor antimicrobial activities. The organic extracts were more active against cancer cells than the aqueous extracts, while the aqueous extracts were more potent as antioxidants than the organic extracts. Overall, the mushroom extract from the durian substrate was the most effective except against A549 and SW948, while the aqueous extract from the durian substrate was the most effective against the A549 cancer cell line with 29.53±2.39% inhibition. On the other hand, the organic mushroom extract from the sawdust substrate was the most effective against SW948 with 60.24±2.45 % inhibition. Further studies, however, are needed to elucidate the molecular mechanism of action of P. pulmonarius extracts against cancer cell proliferation and the effect of the substrates on the nutritional composition, secondary metabolites, and other biological activities of P. pulmonarius extracts.